Paper-based Microfluidic Devices for the Analysis of Various Pathogens from Diverse Samples - Singh, Namita Ashish; Rai, Nitish; Singh, Ashish Kumar; Jain, Vidhi; Narang, Jagriti (Current Analytical Chemistry, 2024)
In today's era, detection of disease is utmost important for the management of disease. Early detection leads to early management of disease. Paper-based microfluidic devices are promising technologies that are cost-effective, portable and easy to use over conventional methods. In addition, paper-based microfluidics offers low reagent/sample volume, less response time and can be used in resource-limited settings. Researchers are highly fascinated by this technology as it has a lot of potential to convert into commercial monitoring devices. The present article covers the uses of paper-based microfluidic technology for the swift and sensitive detection of pathogens from diverse samples, viz. food, water and blood. In this comprehensive review, paper-based microfluidic devices are introduced, including the basic concepts, current status and applications, along with the discussion of the limitations of microfluidics for the detection of pathogens. Although paper-based microfluidic devices are being developed, their commercialization requires simplification of manufacturing processes, reduction in production costs as well as an increase in production efficiency. Nonetheless, the integration of artificial intelligence (AI) and the Internet of Things (IoT) like smartphones, digital cameras, webcam etc. with paper-associated diagnosis has transformed the point-of-care (POC) diagnostics.
Keywords: water